PUPIL CYCLE TIME AND PERIPAPILLARY PERFUSION IN ANGLE CLOSURE GLAUCOMA - Kamal, Muhammad Alfin; Rahmi, Fifin L.; Puspasari, Denti; Maharani, Maharani (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction and Objective: One of important roles in the pathogenesis of glaucoma is vascular condition. To enhance glaucoma management, the clinical assessment of ocular perfusion is required. The pupillary light reflex's afferent or efferent pathways may become impaired as a result of pupil cycle time (PCT) elongation. PCT is a simple objective method to measure the function of optic nerve, including glaucoma. The purpose of this study is to evaluate the connection between pupil PCT and peripapillary perfusion. Methods: A cross-sectional study from Kariadi Hospital included 26 eyes with angle closure glaucoma and 26 eyes of healthy patients. Complete ophthalmologic examinations, PCT measurements, and OCT peripapillary angiography were performed on each patient. Patients with history of drugs use that can affect pupillary reflexes such as barbiturates, methyldopa, anaesthetics, and antidepressant, and patients with history of glaucoma attack are excluded. The comparisons between the two groups were examined, with a p<0.05 indicating statistical significance. Results: The mean PCT of normal subjects was 943,4ms (882,4ms – 993,4ms) and angle closure glaucoma subject was 1789,5ms (1060ms – 4600ms). There were statistically significant difference of PCT value in angle closure glaucoma compared to normal subjects (P<0,05). Peripapillary flow index and peripapillary vessel density in closed angle glaucomatous eyes were lower than normal eyes (P<0.05). There is a significant relationship between PCT with peripapillary flow index and peripapillary vessel density. (P<0,05). Conclusion: In angle closure glaucoma, prolonged PCT associated with decreased peripapillary perfusion as shown by decreases in peripapillary flow index and peripapillary vascular density.